Identification of microplastic in effluents of waste water treatment plants using focal plane array-based micro-Fourier-transform infrared imaging. (1st January 2017) - Mintenig, S.M.; Int-Veen, I.; Löder, M.G.J.; Primpke, S.; Gerdts, G.
Abstract: The global presence of microplastic (MP) in aquatic ecosystems has been shown by various studies. However, neither MP concentrations nor their sources or sinks are completely known. Waste water treatment plants (WWTPs) are considered as significant point sources discharging MP to the environment. This study investigated MP in the effluents of 12 WWTPs in Lower Saxony, Germany. Samples were purified by a plastic-preserving enzymatic-oxidative procedure and subsequent density separation using a zinc chloride solution. For analysis, attenuated total reflection Fourier-transform infrared spectroscopy (ATR-FT-IR) and focal plane array (FPA)-based transmission micro-FT-IR imaging were applied. This allowed the identification of polymers of all MP down to a size of 20 μm. In all effluents MP was found with quantities ranging from 0 to 5 × 10 1  m −3  MP > 500 μm and 1 × 10 1 to 9 × 10 3  m −3  MP < 500 μm. By far, polyethylene was the most frequent polymer type in both size classes. Quantities of synthetic fibres ranged from 9 × 10 1 to 1 × 10 3  m −3 and were predominantly made of polyester. Considering the annual effluxes of tested WWTPs, total discharges of 9 × 10 7 to 4 × 10 9  MP particles and fibres per WWTP could be expected. Interestingly, one tertiary WWTP had an additionally installed post-filtration that reduced the total MP discharge by 97%. Furthermore, the sewage sludge of six WWTPs was examined and the existence of MP, predominantly polyethylene, revealed. Our findings suggest that WWTPs could be a sink but also a source of MP and thus can be considered to play an important role for environmental MP pollution. Graphical abstract: Highlights: Microplastic (MP) was analysed in effluents from 4 tertiary and 8 secondary WWTPs. Micro-FT-IR imaging allowed polymer identification of all MP down to a size of 20 μm. MP was determined in all effluents of examined WWTPs. An installed post-filtration (tertiary treatment) removed 97% of MP. WWTP may act as MP source but also as sink since MP was detected in sewage sludge.